An evaluation of mindful clinical congruence in medical students after course-based teaching - Hutchinson, Tom A; Hanley, James A; Liben, Stephen; Lubarsky, Stuart (Canadian Medical Education Journal, 2024)
Purpose: We questioned whether an intensive experiential core course would change medical students’ intention to practice mindful clinical congruence. Our primary hypothesis was that we would see more of a change in the intention to practice mindful clinical congruence in those who had taken versus not yet taken our course. Methods: From a class of 179 in second year we recruited 57 (32%) students who had been already divided into three groups that completed the course in successive periods. We measured mindful clinical congruence using a questionnaire developed and evaluated for validity. We also measured students’ level of stress to determine if any effects we saw were related to stress reduction. Results: Students who had just completed the course showed a greater intention to practice mindful clinical congruence than students who had not yet started the course. There was an apparent slight increase in perceived stress in those who had completed our course. Conclusions: We can change students’ intention to practice mindfully and congruently, which we believe will prevent a decline in compassion and ethical values in clerkship. The results did not appear to be explained by a decrease in stress in students who completed the course.